2015
DOI: 10.3389/fmicb.2015.00617
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial nisin acts against saliva derived multi-species biofilms without cytotoxicity to human oral cells

Abstract: Objectives: Nisin is a lantibiotic widely used for the preservation of food and beverages. Recently, investigators have reported that nisin may have clinical applications for treating bacterial infections. The aim of this study was to investigate the effects of ultra pure food grade Nisin ZP (>95% purity) on taxonomically diverse bacteria common to the human oral cavity and saliva derived multi-species oral biofilms, and to discern the toxicity of nisin against human cells relevant to the oral cavity.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 89 publications
(101 reference statements)
12
139
2
6
Order By: Relevance
“…Shin et al . () also reported that nisin exerted anti‐biofilm effects on saliva derived multispecies biofilms without causing cytotoxicity to human oral cells (Fig. ).…”
Section: Nisin and Oral Healthmentioning
confidence: 75%
See 3 more Smart Citations
“…Shin et al . () also reported that nisin exerted anti‐biofilm effects on saliva derived multispecies biofilms without causing cytotoxicity to human oral cells (Fig. ).…”
Section: Nisin and Oral Healthmentioning
confidence: 75%
“…; Shin et al . ). Similar to other lantibiotics, nisin contains several unusual amino acids as a result of enzymatic post‐translational modifications (Sahl et al .…”
Section: Nisin: a Bacterially Derived Antimicrobialmentioning
confidence: 97%
See 2 more Smart Citations
“…However, more detailed microbial studies are needed to measure the specific alterations in the oral microbiome before and after nisin use, since it is important to maintain oral commensal bacteria while selectively removing the pathogenic microbes. Recently, 2 studies examined the effects of a highly purified form of nisin on oral salivary‐derived biofilms and planktonic forms of oral gram‐positive and gram‐negative oral bacteria, including Porphyromonas gingivalis , Prevotella intermedia , A. actinomycetemcomytans , Treponema denticola , and Enterococcus faecalis . Nisin inhibited the planktonic growth of these pathogenic bacteria significantly at concentrations ranging from 2.5 to 50 μg/ml, and the inhibitory effects increased with increasing concentrations of nisin up to 200 μg/ml.…”
Section: Nisin‐producing Lactococcus Lactis Probiotic and Nisin Are Pmentioning
confidence: 99%